Sustaining the export of mango and banana through value-chain development - Damodaran, T; Beer, Karma; Mishra, Maneesh; Singh, Akath (Indian Horticulture, 2026)
Mango and banana are high-value tropical fruits critical to South and Southeast Asian economies and diets. Subtropical production faces challenges including variable climates, irregular fruiting, cultivar-specific postharvest sensitivity, and fragmented smallholder value chains, leading to low farm-gate prices and high losses. Key gaps include limited pre- and postharvest technologies, weak cold chain and controlled-atmosphere capacity, inconsistent grading, low processing adoption, and poor market and finance access. Addressing these requires four pillars: improved on-farm practices, cost-effective postharvest interventions, value addition, and enabling systems. Scalable pilots, public–private partnerships, and gender-inclusive approaches can enhance efficiency, reduce losses, and increase farmer incomes.